2003
DOI: 10.1111/j.1349-7006.2003.tb01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox gene expression and mutation in cervical carcinoma cells

Abstract: An association between deregulation of homeobox (HOX) gene expression and oncogenic transformation has been recently reported in human tumors. In this study, we investigated HOX gene expression and mutation in cervical carcinoma cells. Using reverse transcription-PCR, 11 human cervical carcinoma cell lines and 14 normal cervical tissue samples were examined for mRNA expression of the 39 class I HOX genes. DNA samples from 11 cell lines were tested for mutations in exons 1 and 2 of the HOXA10 and A13 genes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
1
27
1
2
Order By: Relevance
“…Thus, in recent years, much effort has been devoted to the study of HOX genes and proteins and their link with cancer (Shah and Sukumar, 2010). In cervix, despite some evidences of HOX member modulation (Alami et al, 1999;Hung et al, 2003;Lopez et al, 2006b;Gonzalez-Herrera et al, 2015), the participation of these transcription factors in cervical carcinogenesis has not been explored in depth. In this work, we evaluated HOX gene deregulation in CC; in particular, we focused on HOXA9 modulation and whether this phenomenon results in an advantage for the CC cell.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in recent years, much effort has been devoted to the study of HOX genes and proteins and their link with cancer (Shah and Sukumar, 2010). In cervix, despite some evidences of HOX member modulation (Alami et al, 1999;Hung et al, 2003;Lopez et al, 2006b;Gonzalez-Herrera et al, 2015), the participation of these transcription factors in cervical carcinogenesis has not been explored in depth. In this work, we evaluated HOX gene deregulation in CC; in particular, we focused on HOXA9 modulation and whether this phenomenon results in an advantage for the CC cell.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in gynecological field, there have been several reports suggesting that the abnormal expression of particular HOX genes is associated with cervical, ovarian, and endometrial cancers. [16][17][18][19] As for the cervical cancers, several studies have shown a different pattern of expression of specific HOX genes between normal cervix and cervical cancer, including a report which analyzed 39 HOX gene expression profiles. 16 Unfortunately, there have been no studies performing such a comprehensive analysis of the different expression of HOX genes between normal ovary and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] As for the cervical cancers, several studies have shown a different pattern of expression of specific HOX genes between normal cervix and cervical cancer, including a report which analyzed 39 HOX gene expression profiles. 16 Unfortunately, there have been no studies performing such a comprehensive analysis of the different expression of HOX genes between normal ovary and ovarian cancer. In the current study, we created expression profile of 36 HOX genes using ovarian-derived samples and determined which genes were over-expressed in ovarian cancer cell lines or tissues as compared to normal ovarian tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gynecologic field, there are several reports describing that abnormal expression of particular HOX genes seems to be involved in cervical, ovarian and endometrial neoplasms (23)(24)(25)(26) including a recent report by Zhao et al (27). In the context of embryonic development, the expression of invasive characteristics of cancer cells might be a similar phenomenon, analogous to the movement of normal embryonic cells mediated by expression of HOX genes.…”
Section: Introductionmentioning
confidence: 99%